Validating the performance of the HVAC system for commercial buildings - Goel, Swati; Manikandan, R (International Journal of Engineering and Technology, 2018)
Commercial Buildings consumes a large amount of world’s energy. Energy components comprises of Lighting, Heating, Cooling, Ventilation, water heating etc. To make the building energy efficient, we need to maintain, monitor and apply thermal optimization. Numerous researchers over the world are chipping away at vitality demonstrating and control with a specific end goal to create techniques which will bring about general decrease of vitality utilization. This paper presentstheworkflow of the energy modelling HVAC (heating, ventilation and cooling)systemwhich proved to be the complete solution for low energy buildings.Also the estimation of the thermal load which helps in validation of architectural design for energy efficient buildings.